Endovascular treatment of intrarenal aneurysms bleeding and angiomyolipomas in a patient with tuberous sclerosis and polycystic kidney disease - Túlio Leite; Lucas Vatanabe Pazinato; Maria Juliana de Aquino Vidal; Danielo de Freitas; Joaquim Mauricio da Motta Leal Filho (Brazilian Journal of Nephrology, 2021)
Abstract Tuberous sclerosis complex (TSC) and autosomal dominant polycystic kidney disease (ADPKD) are conditions related to renal failure that can rarely occur in association as a contiguous gene syndrome. Angiomyolipomas (AMLs) are renal tumors strongly related to TSC that may rupture and cause life-threatening bleedings. We present a patient with TSC, ADPKD, and renal AMLs with persistent hematuria requiring blood transfusion. The persistent hematuria was successfully treated through endovascular embolization, a minimally invasive nephron sparing technique.